Essential Astrophysics - Lang, Kenneth R. (Springer, 2013)
Essential Astrophysics is a book to learn or teach from, as well as a fundamental reference for anyone interested in astronomy and astrophysics. This unique volume can be used as a textbook, teaching guide, or reference source for just about anyone interested in astronomy and astrophysics. It serves as a comprehensive, introductory text, which takes the student through the field of astrophysics in lecture-sized chapters of basic physical principles applied to the cosmos. Undergraduate students with an interest in the physical sciences, such as astronomy, chemistry, engineering, or physics, will enjoy this one-semester overview. The text is of sufficient breadth and depth to prepare the interested student for more advanced, specialized courses in the future. The clarity and comprehensive nature of Essential Astrophysics make it a significant resource for the curious reader that is unfamiliar with astrophysics or for professional astronomers who may have forgotten the basics. Astronomical examples are provided throughout the text, to reinforce the basic concepts and physics, and to demonstrate the use of the relevant formulae. In this way, the student learns to apply the fundamental equations and principles to cosmic objects and situations. All of the example problems are solved with the rough accuracy needed to portray the basic result. Such order-of-magnitude estimates are commonly used in astronomy and astrophysics, where large numbers are involved, and an understanding of the underlying physics does not require engineering accuracy. Essential Astrophysics is a serious introduction to astrophysics complete with the necessary formulae. These equations sometimes include the calculus of integration, or adding up, and differentiation, that are found in the author’s classic Astrophysical Formulae and more advanced textbooks. Nevertheless, the end result in Essential Astrophysics is always a simple algebraic relationship that can be applied to cosmic objects. These fundamental equations are given in the text and collected at the end of the book in Appendix III, for future reference and use. Therefore, only elementary algebra is required to solve any of the example problems or other numerical conclusions in this book.